Oxidative Stress and Hypoxia Contribute to Alzheimer's Disease Pathogenesis: Two Sides of the Same Coin. (2009) - Guglielmotto, Michela; Tamagno, Elena; Danni, Oliviero
Abstract : While it is well established that stroke and cerebral hypoperfusion are risk factors for Alzheimer's disease (AD), the molecular link between ischemia/hypoxia and amyloid precursor protein (APP) processing has only been recently established. Here we review the role of the release of reactive oxygen species (ROS) by the mitochondrial electron chain in response to hypoxia, providing evidence that hypoxia fosters the amyloidogenic APP processing through a biphasic mechanism that up-regulates β-secretase activity, which involves an early release of ROS and an activation of HIF-1α.